Advancing sustainable materials and technologies - Putra Jaya, Ramadhansyah; Munirwan, Reza Pahlevi; Bunyamin, Bunyamin (Popular Scientist, 2025)
This second volume (2025) brings together a collection of review and research articles focused on sustainable innovations in construction materials and geotechnical engineering. The first article by Mahi et al. [1] reviews the potential of biochar as a sustainable cement replacement, highlighting its ability to improve mechanical and durability properties of concrete composites. Their research demonstrated that biochar can enhance early-age compressive strength, with the most significant improvements observed at lower replacement levels (approximately 2–5%). Moreover, flexural and tensile strengths showed moderate increases depending on the biochar dosage, feedstock origin, and pre-treatment methods. However, higher replacement levels resulted in strength reductions due to increased porosity and greater water demand